1988
DOI: 10.1093/ajcp/90.3.262
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Hematologic Parameters in Healthy Subjects: Intraindividual versus Interindividual Variation

Abstract: An automated complete blood count with white blood cell differential was performed yearly on successive groups of healthy second-year medical students from 1979 through 1987. For three classes (1984-1987), the counts were repeated on the same people nine months later. These data demonstrated that the mean value of all hematologic parameters was quite stable over nine years. This allowed for an estimation of the upper limit for the combined effects of drift in accuracy, precision, and biologic stability. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…The degree of Hb variability that is present in patients with CKD, including those who are not receiving ESA, is greater than would be expected among patients without uremia (13)(14)(15). Variation of Hb in healthy individuals does occur (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of Hb variability that is present in patients with CKD, including those who are not receiving ESA, is greater than would be expected among patients without uremia (13)(14)(15). Variation of Hb in healthy individuals does occur (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Variation of Hb in healthy individuals does occur (13)(14)(15)(16). It is both diurnal and fluctuating over periods of time up to 1 yr (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that almost all the cases had Platelet count within the normal range 150,000 to 400,000 per cubic millimetre. [7] Preoperatively the Mean of Platelet count was 261x103 with S.D of 49 and postoperatively 263x103 with S.D of 65. WBC count was also observed to lie in the normal range 4500 to 11000 per cubic millimeter.…”
Section: Resultsmentioning
confidence: 90%
“…Individuals' hematologic parameters are fairly stable over time, especially the PLT count [37][38][39][40]. Dot et al serially assessed several common hematological parameters once per month for a year in 39 healthy volunteers and found that the over-time variation of those parameters was very low.…”
Section: Discussionmentioning
confidence: 99%